Norbornene in Organic Synthesis - Li, Caifeng; Liu, Liu; Fu, Xuegang; Huang, Jianhui (Synthesis, 2018)
The norbornene skeleton possesses an alkene functionality with a fixed conformation, and represents unique reactivity. The use of norbornene and analogues as substrates is overviewed; reactivities are discussed as well as the role of norbornenes as ligands assisting modern organic transformations.1 Introduction2 Synthesis of Substituted Norbornenes2.1 Preparation of Functionalized Norbornenes by Deprotonation and Substitution Reactions2.2 Preparation of Functionalized Norbornenes under Palladium-Catalyzed Reaction Conditions2.3 Alkylation of Norbornene2.4 Multistep Synthesis3 Synthesis of Substituted Norbornanes3.1 Three-Membered-Ring Formation3.2 Formation of Four-Membered Rings3.3 Five- and Six-Membered Ring Formation3.4 Syntheses of Difunctionalized Norbornanes4 Synthesis of Cyclopentanes4.1 Oxidation Reactions4.2 Ring-Opening Cross Metathesis (ROCM)4.3 Ring-Opening Metathesis Polymerization (ROMP)4.4 Palladium-Catalyzed Ring-Opening of Norbornene5 Norbornene-Mediated Reactions5.1 Palladium Insertion into Carbon–Halide Bonds5.2 Palladium Insertion into N–H and C–H Bonds5.3 Norbornene as Ligand in Mediated Reactions6 Conclusion
Keywords: norbornene; C–H activation; norbornane; ring-opening metathesis